A Descriptive Case Study: Exploring Drawing Art Therapy in Building Self-Esteem Among Patients with Chronic Low Self-Esteem - Adinda Nurnilamsari; Laura Khattrine Noviyanti (Global Health Science Group, 2026)
Chronic low self-esteem is a common type of mental disorder characterized by negative feelings towards oneself due to perceived shortcomings. This condition is often caused by negative judgment, both from oneself and the environment. One nursing intervention that can be used to improve self-esteem is drawing art therapy. Drawing art therapy allows patients to channel negative emotions into works of art and gain self-confidence through positive achievements in preferred activities. This writing aims to identify a decrease in signs and symptoms of rednah self-esteem using observation sheets before and after being given drawing art therapy. The method used is descriptive case study. With the criteria that patients are cooperative and do not experience verbal communication disorders. Data for this descriptive case study were collected through involving in-depth interviews, participant observation, and clinical documentation. The collected data were analyzed using descriptive-qualitative analysis. This process involved reducing interview transcripts and observation notes, followed by a thematic review of the patient's drawings to identify psychological shifts. The effectiveness of the therapy was determined by comparing the frequency of signs and symptoms before and after the 5-day intervention.The results of nursing evaluation after 5 days of intervention showed a decrease in signs and symptoms of low self-esteem from 14 to 8. This shows that drawing art therapy is effective in increasing self-esteem in patients with chronic low self-esteem.